THE EFFECT OF SUBTITUTION FEED ON THE GROWTH AND SURVIVAL RATE OF LARVAE BAUNG (HEMIBAGRUSNEMURUS) - Zulmi Arnoli; Nuraini Nuraini; Sukendi Sukendi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT This research was conducted on January - February 2018 in the Laboratory of Fish Hatchery and Breeding Faculty of Fisheries and Marine, University of Riau. The purpose of this research was to Effect Of Subtitution Feed On The Growth and Survival Rate of Larvae Baung (Hemibagrusnemurus). This research used the experimental method, while the experimental design using Completely Randomized Design (CRD) with 6 treatments, each with 3 replication. The composition of the treatment P1 (Tubifex sp. 1-30 days), P2 (Earthworms 1-30 days), P3 (Shrimp pellet 1-30 days), P4 (Tubifex sp.1-15days + Earthworms 16-30 days), P5 (Earthworms 1-15 days + Shrimp pellet 16-30 days), P6 (Tubifex sp 1-10 days + Earthworms 11-20 days + Shrimp pellet 21-30 days).The best result of the treatments from this research with given Tubifex sp. on 1-15 days and subtitution with earthworm feed for 16-30 days with 0,63 g (weight), 3,23 cm (length), 12,56% per days (specific growht rate) and 84,44% survival rate of larvae. The water quality parameters during this research were: temperature26,7-28,7oC,pH 5,3-6,3and dissolved oxygen 4,0 -5,4 mg/L. Key words: Subtitution, Hemibagrus nemurus,earthworm, growth and survival